Negative molecular ions of azafullerenes and their hydrogenated derivatives - Vasil’ev, Yu; Abzalimov, R.; Nasibullaev, Sh.; Tuktarov, R.; Hauke, Frank; Reuther, Uwe; Hirsch, Andreas; Drewello, Thomas (Physics of the Solid State, 2002)
The formation and decay of negative molecular ions of azafullerenes and their hydrogenated derivatives are investigated by mass spectrometry. The mechanisms of resonant electron capture and the lifetimes of negative molecular ions with respect to the electron autodetachment in azafullerene molecules are discussed, A comparative analysis of the data obtained for azafullerenes and hydrogenated fullerene derivatives is carried out. © 2002 MAIK "Nauka/Interperiodica".